Currency Substitution : The Recent Experience of Bolivia - Clements, Benedict (IMF Working Papers; Working Paper ;, 1992)
This paper analyzes the determinants of currency substitution in Bolivia in the period following the 1984/85 hyperinflation. We find that expected exchange rate depreciation and actual interest rate differentials between boliviano and dollar deposits in the Bolivian banking system are statistically significant determinants of the degree of currency substitution. However, the explanatory power of these variables is low compared to variables that measure the degree of inertia in the currency substitution process. Thus, further reductions in inflation or higher interest rates for boliviano bank deposits are likely to have but a small effect on dollarization.